The Role of Private Investment in Renewable Energy Projects - Bojko, David (2025)
This thesis provides an overview of private equity (PE) and venture capital (VC) funds, focusing on their structure, objectives, and role in financing renewable energy projects. It examines how these funding sources support innovation, project development, and scaling within the clean energy sector. The theoretical part introduces ratio analysis as a method for assessing company performance, especially where traditional profitability metrics may be limited or inapplicable. The practical part applies this framework to a comparative case study of two companies - Microvast and EnerSys - active in the energy storage segment. Using liquidity, leverage, efficiency, profitability, and market valuation ratios, the analysis highlights the financial differences between a venture and later PE-backed, growth-oriented firm and a mature, publicly traded manufacturer. The main findings underline how funding stage, capital structure, and investor expectations are reflected in financial ratios and valuation metrics.